(untitled) (New York, NY, 2005)
In this volume, methodologies for establishing what constitutes expert practice in language teaching and learning are discussed and the contributions address the fields of listening, reading, writing, speaking and communication strategies, looking at common characteristics of the "expert teacher" and the "expert learner."
Keywords: Second language acquisition.,Language and languages,Competence and performance (Linguistics); Study and teaching